2020
DOI: 10.1002/cb.1832
|View full text |Cite
|
Sign up to set email alerts
|

Nostalgia prompts sustainable product disposal

Abstract: Consumers' product-disposal behaviors impact the environment, businesses, society, and consumer well-being. This research explores if and how consumers' disposal behaviors are influenced by sentiments of nostalgia. Four experimental studies are conducted, two on student samples and two on general population, to test our hypotheses. Study 1 shows that compared with collective nostalgia, personal nostalgia elicits higher intention to keep and reuse products. In contrast, collective nostalgia elicits higher inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 65 publications
2
26
0
1
Order By: Relevance
“…The next four papers, albeit using different research approaches, are related in some way to consumers' product disposal and reuse behaviours and their impact on the environment. Wang, Tian, Sarigöllü, and Xu (2020) conduct four experimental studies to examine the role of nostalgia (longing for the past) in explaining sustainable disposal behaviour. Their findings show that whilst evoking different types of nostalgia leads to different choices in product disposal (keep, reuse, donate and recycle), both personal and collective nostalgia reduce intention to throw products away.…”
mentioning
confidence: 99%
“…The next four papers, albeit using different research approaches, are related in some way to consumers' product disposal and reuse behaviours and their impact on the environment. Wang, Tian, Sarigöllü, and Xu (2020) conduct four experimental studies to examine the role of nostalgia (longing for the past) in explaining sustainable disposal behaviour. Their findings show that whilst evoking different types of nostalgia leads to different choices in product disposal (keep, reuse, donate and recycle), both personal and collective nostalgia reduce intention to throw products away.…”
mentioning
confidence: 99%
“…One study used structural equation modeling to examine how nostalgia affects tourists' pro-environmental behavior through subjective attitudes, perceived behavioral control, subjective norms, and meaning in life (Wu et al, 2020 ). Two studies revealed that personal nostalgia increases the likelihood of retaining and reusing products to protect nature (Wang et al, 2020 ; Zhang et al, 2021 ). Thus, we propose the following hypotheses:…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…Thus, collective efficacy is not the ability of the group itself, but the individual’s perception of the collective ability. When a majority of the group expresses support and appreciation for prosocial activities, individuals respond to others’ prosocial behavioral expectations by adjusting their behavioral willingness to participate in environmental protection activities ( Bamberg et al, 2015 ), plastic reduction ( Reese and Junge, 2017 ), and recycling activities ( Wang et al, 2020 ), etc.…”
Section: Theoretical Backgroundsmentioning
confidence: 99%